Penerapan Pendekatan CRT untuk Meningkatkan Kemampuan Berpikir kritis pada Mata Pelajaran IPAS Kelas IV SDN Gayamsari 02 Semarang - Naufanda, Muchammad Fitra; Dwijayanti, Ida; Izzah, Khodijah Habibatul (Melati Institute, 2024)
This research uses a combination research method (mixed method). The population in this study were all fourth grade students totaling 28 students. The research sample for this quantitative method took all students and for the qualitative method took 3 students as research subjects. Data were collected using questionnaires, interviews, and observations. The data analysis technique used in quantitative method research is using percentages and in qualitative methods using the Miles and Huberman model data analysis technique. The application of the Culturally Responsive Teaching (CRT) approach can improve students' critical thinking skills. From the results of the analysis, as many as 19 students or 67% of fourth grade students of SD Negeri Gayamsari 02 got the ability criteria (critical thinking).